2015
DOI: 10.1039/c5ra12540e
|View full text |Cite
|
Sign up to set email alerts
|

Side chain structure affects the molecular packing and photovoltaic performance of oligothiophene-based solution-processable small molecules

Abstract: In this study we synthesized a series of solution-processable small molecules comprising 2,2 0 -bithiophene (BTh), terthiophene (TTh), and thiobarbituric acid (TB) units as the central core, p-conjugated spacer, and acceptor end-capping moieties, respectively, but with alkyl side-chains of different lengths presented from their central BTh units (TBTThBTh-H, TBTThBTh-C4, TBTThBTh-C8, TBTThBTh-C12). We then investigated the structure-property relationships of these compounds in terms of their packing behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 66 publications
0
9
1
Order By: Relevance
“…In addition, another weak signal for π-stacking at 1.75 Å –1 for the ArSiID film in the OP direction was also detected. We suggest that two types of π-stacking configurations coexisted within the ArSiID film because the d -spacings of these two peaks for each molecule could not be classified into a set of (010) plane . The more intense π-stacking and higher intensity of the peak near 0.37 Å –1 in the IP direction of pristine ArSiID film than that seen in ArSiID-F and ArSiID-Cl imply the higher crystallinity of ArSiID as compared to those of ArSiID-F and ArSiID-Cl .…”
Section: Resultscontrasting
confidence: 99%
“…In addition, another weak signal for π-stacking at 1.75 Å –1 for the ArSiID film in the OP direction was also detected. We suggest that two types of π-stacking configurations coexisted within the ArSiID film because the d -spacings of these two peaks for each molecule could not be classified into a set of (010) plane . The more intense π-stacking and higher intensity of the peak near 0.37 Å –1 in the IP direction of pristine ArSiID film than that seen in ArSiID-F and ArSiID-Cl imply the higher crystallinity of ArSiID as compared to those of ArSiID-F and ArSiID-Cl .…”
Section: Resultscontrasting
confidence: 99%
“…Finally, it should be noted that lowering the HOMO energy levels of conjugated polymers via increasing the bulkiness of the side chains was observed previously . However, lack of systematic side chain variation in these studies did not allow one to reveal clearly the supramolecular nature of the observed effects.…”
Section: Resultsmentioning
confidence: 74%
“…Therefore, before OSC devices were fabricated, an investigation of various post-deposition techniques was applied to thin films of compound 1 . It has been demonstrated that compounds with linear alkyl chains promote greater organization in active layers and improve device performance [ 41 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and therefore only compound 1 with the octyl side chain was investigated. All thin films of 1 were cast from 2-MeTHF.…”
Section: Resultsmentioning
confidence: 99%